A novel LAMB2 gene mutation associated with a severe phenotype in a neonate with Pierson syndrome. Issue 1 (December 2016) - Zemrani, Boutaina; Cachat, François; Bonny, Olivier; Giannoni, Eric; Durig, Jacques; Fellmann, Florence; Chehade, Hassib
Abstract Background Pierson syndrome (PS) is a rare autosomal recessive disorder, caused by mutations in the laminin β2 (LAMB2) gene. It is characterized by congenital nephrotic syndrome, microcoria, and neurodevelopmental deficits. Several mutations with genotype–phenotype correlations have been reported, often with great clinical variability. We hereby report a novel homozygous nonsense mutation in the LAMB2 gene, associated with a severe phenotype presentation. Case diagnosis We describe a term male infant born from consanguineous parents. The mother previously lost three children in the neonatal period, secondary to undefined renal disease, had two spontaneous abortions, and gave birth to one healthy daughter. The index case presented at birth with bilateral microcoria, severe hypotonia, respiratory distress, and congenital nephrotic syndrome associated with anuria and severe renal failure requiring peritoneal dialysis. The patients' clinical follow-up was unfavorable, and the newborn died at 7 days of life, after withdrawal of life support. Genetic analysis revealed a homozygous nonsense mutation at position c.2890C>T causing a premature stop codon (p.R964*) in LAMB2 gene. Conclusion We here describe a novel nonsense homozygous mutation in LAMB2 gene causing a severe neonatal presentation of Pierson syndrome. This new mutation expands the genotype–phenotype spectrum of this rare disease and confirms that truncating mutations might be associated with severe clinical features.